1971
DOI: 10.1073/pnas.68.1.20
|View full text |Cite
|
Sign up to set email alerts
|

Hypoglycin A: A Specific Inhibitor of Isovaleryl CoA Dehydrogenase

Abstract: Evidence is presented for the specific in vivo and in vitro inhibition of isovaleryl CoA dehydrogenation by hypoglycin A and its derivative, a-ketomethylenecyclopropylpropionic acid. a-MethylbutyrylCoA dehydrogenation was also impaired, but the degree of inhibition was much lower. Isobutyryl CoA dehydrogenation was not inhibited. 4-Pentenoic acid inhibited none of these reactions. It is concluded that isovaleryl CoA is dehydrogenated by a specific enzyme, isovaleryl CoA dehydrogenase, contrary to previous assu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
1
1

Year Published

1975
1975
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(26 citation statements)
references
References 19 publications
(22 reference statements)
0
24
1
1
Order By: Relevance
“…Tanaka et al (25)(26)(27) have shown that hypoglycin inhibits the enzyme isovaleryl-CoA dehydrogenase and probably also glutaryl-CoA dehydrogenase and in rats results in the excretion of isovaleric, glutaric, and several other unusual carboxylic acids. In this respect hypoglycin toxicity and probably Jamaican vomiting sickness differ from pentenoic acid toxicity and Reye's syndrome.…”
Section: T E S T Control T E S T Control T E S T Controlmentioning
confidence: 99%
“…Tanaka et al (25)(26)(27) have shown that hypoglycin inhibits the enzyme isovaleryl-CoA dehydrogenase and probably also glutaryl-CoA dehydrogenase and in rats results in the excretion of isovaleric, glutaric, and several other unusual carboxylic acids. In this respect hypoglycin toxicity and probably Jamaican vomiting sickness differ from pentenoic acid toxicity and Reye's syndrome.…”
Section: T E S T Control T E S T Control T E S T Controlmentioning
confidence: 99%
“…Employing an inhibitor of several acyl-CoA dehydrogenases, MCPA-CoA (2,8,9), we developed an improved assay for isovaleryl-CoA dehydrogenase to accurately determine residual isovaleryl-CoA dehydrogenase activity in fibroblasts of patients with clinically severe and mild forms of isovaleric acidemia.…”
Section: Abbreviationmentioning
confidence: 99%
“…10,14 In vivo MCPA is transformed to a coenzyme A (CoA) ester and, in this form, it binds to multiple acyl-CoA dehydrogenases, 4,[6][7][8] without further metabolization. Enzymes loaded with MCPA-CoA are blocked and no longer available for degradation of fatty acids in the mitochondrial ß-oxidation pathway.…”
Section: Introductionmentioning
confidence: 99%